Teacher Professionalism in the Era of Educational Transformation: Analysis Based on Data-Driven Planning, Digital Competence, and Principal Leadership - Miming Juneri; Maya Novita Sari (Journal of Educational Sciences, 2026)
This study analyzes the simultaneous influence of data-driven planning, digital competence, and principal leadership on teacher professionalism. The study employed a quantitative, ex-post facto design. The population consisted of 250 individuals, and the researchers selected a sample of 72 using Slovin's formula at a 10% margin of error. The researchers tested the instrument on 30 teachers outside the study sample. Data were collected through questionnaires and analyzed using SPSS 26, covering descriptive and inferential statistics (classical assumption tests and hypothesis testing). The results indicate that all three variables positively and significantly influence teacher professionalism. Each variable contributes differently: 0.297 for data-driven planning, 0.261 for digital competence, and 0.446 for leadership. This indicates that principal leadership has the dominant influence on teacher professionalism. Collectively, the independent variables exert a positive and significant influence of 28.6% on teacher professionalism. These findings show that teacher professionalism is influenced not only by teachers' ability to use digital technology but also by the principal's capacity for effective school leadership and the implementation of data-driven planning as a foundation for decision-making to improve educational quality.